IMPLEMENTASI KERJASAMA ANTARA UNITED NATIONS INDUSTRIAL DEVELOPMENT ORGANIZATION (UNIDO) DAN INDONESIA DALAM MENINGKATKAN INDUSTRI PERIKANAN INDONESIA DAN MENCAPAI PEMBANGUNAN BERKELANJUTAN TARGET 9 - Dessy Natalia (2020)
The United Nations Industrial Development Organization (UNIDO) is an organization under the auspices of the United Nations (UN) which is engaged in industry. The main objective of this organization is to improve the industrial sector in developing countries and countries with transition economies. UNIDO as an organization that deals directly with increasing industrial activity takes a very important position on this issue coupled with its purpose attached to the balance between industry and the sustainability of nature. This shows that industrial activities can still be carried out without sacrificing nature. One of the leading sectors of Indonesia, namely the fishing industry, has a great wealth, but the use and promotion has not been carried out optimally and if left unchecked, it will have negative impacts and damage the nature itself. The fisheries sector is also the livelihood of coastal communities so that it can be an indicator for poverty reduction which is the goal of the United Nations in 2030. In making this research, the authors use the concept of Inclusive and Sustainable Industrial Development (ISID) and international cooperation for analysis. This research was made to find out how the implementation of cooperation between UNIDO and Indonesia in improving the Indonesian fishing industry through the Indonesian SMART-Fish program and to find out whether the implementation of the SMART-Fish program is in accordance with the principles of sustainable industry in order to achieve sustainable development. This research method uses a descriptive qualitative research approach (literature study) which describes the research problem empirically.